Genetics and breeding for disease resistance of livestock - Pal, Aruna; Chakravarty, A. K. (London, United Kingdom : Academic Press, an imprint of Elsevier, 2020)
Genetics and Breeding for Disease Resistance of Livestock is a solid resource that combines important information on the underlying genetic causes and governing factors for disease resistance in food animals and applications for breeding purposes. It describes genomics at each species level to help researchers and students understand disease resistance and immunology with the help of genomics, and its application in breeding for disease resistance in an easy way. This is a useful reference for researchers to easily understand and undergo further research in immunology and disease resistance for livestock and is filled with novel applications and research materials for a wide audience, such as students, teachers, academicians, researchers, and industry professionals in diagnostic labs. --
I. Overview of disease resistance: Overview and concept of disease resistance -- Major diseases of livestock and poultry and problems encountered in controlling them -- Disease-resistant traits : analytic tools and indicator traits -- Basic concepts of immunogenetics. -- II. Genetics and genomics for disease resistance: Genetics for innate immunity -- Genetics for adaptive immunity -- Immune-response genes pertaining to livestock species -- Techniques to study immune-response genes -- Genes conferring immunity against bacterial infections -- Genes conferring immunity against viral infections -- Genes conferring immunity against prion infections -- Genes conferring immunity against fungal infections -- Genes conferring immunity against parasitic infections -- Advanced genomic techniques for studying immune-response genes -- Strategies for exploiting immune-response genes to impart disease resistance to livestock -- Breeding for disease resistance based on phenotypic and genotypic traits -- Heritability, repeatability, and genetic correlation of disease-resistance traits -- Selection of livestock and poultry for disease resistance -- Disease resistance for different livestock species -- Breeding strategies for the development of a disease-resistant stock of livestock -- Advanced breeding techniques -- Disease-resistant livestock populations : their development and impact on farm economics.
Includes bibliographical references and index.
Keywords: Livestock -- Breeding; Livestock -- Genetics; Livestock -- Breeding; Livestock -- Genetics